Adenoma detection rate as a quality indicator for colonoscopy: a descriptive cross-sectional study from a tertiary care hospital in Pakistan - Yousaf, Mian Shah; Shafqat, Shameel; Gill, Roger Christopher; Khursheed, Asfia Arham; Parkash, Om (Endoscopy International Open, 2020)
Background and study aims Adenoma detection rate (ADR) is validated for measuring quality of colonoscopy, however there is lack of colorectal cancer (CRC) screening program in South Asia. The purpose of this study is to analyze and review the polyp detection rate (PDR) and ADR and provide insight into the factors that influence them in Pakistan.Patients and methods This retrospective, cross-sectional study was performed at the Aga Khan University Hospital, Karachi, Pakistan, on patients ≥ 18 years, who underwent colonoscopy between January 1, 2017 and June 30, 2018.Results Of 1985 patients, 59 % were male and 41 % female, with mean age of 47.8 ± 16.2 years. The most common indication for colonoscopy was bleeding-per-rectum (28.0 %) and overall PDR and ADR were 17.9 % and 9.9 %, respectively. There was no significant difference between genders for either PDR (P = 0.378) or ADR (P = 0.574). Significantly higher PDR and ADR were found for patients ≥ 50 years (P < 0.001), as well as for suboptimal bowel preparation [PDR (25.7 %; P = 0.007) and ADR (18.6 %; P = 0.014)]. Interestingly, endoscopists with < 500 colonoscopy-procedural-experience reported a higher PDR (21.6 %; P = 0.020) and ADR (14.4 %; P = 0.049), corresponding to a significantly higher PDR (20.6 %; P = 0.005) and ADR (11.7 %; P = 0.02) for endoscopists in practice for ≤ 10 years.Conclusions We have noticed low PDR and ADR, which require further investigation and research. In addition, we believe there should be a different baseline ADR and PDR as a quality indicator for colonoscopy in our region, where no internationally recommended colonoscopic screening programs have been implemented.